\[\begin{equation*} \Pr(\lnot p) = 1 - \Pr(p). \end{equation*} \]
See: negation
Proof. \(p \lor \lnot p\) is a tautology per
\[\begin{equation*} p \lor \lnot p = \begin{cases} 0 \lor \lnot 0 = 0 \lor 1 = \boxed{1} & p = 0 \\ 1 \lor \lnot 1 = 1 \lor 0 = \boxed{1} & p = 1, \\ \end{cases} \end{equation*} \]
and \(p\) is mutually exclusive with \(\lnot p\) per
\[\begin{array}{c|l} p & \lnot p \\ \hline \boxed{0} & \lnot 0 = \boxed{1} \\ \boxed{1} & \lnot 1 = \boxed{0} \> , \end{array} \]
so, we have
\[\begin{align*} \Pr(p \lor \lnot p) & = 1 && \text{per axiom 2} \\ \Pr(p) + \Pr(\lnot p) & = 1 && \text{per axiom 3} \\ \Pr(\lnot p) & = 1 - \Pr(p) && \text{subtract \(\Pr(p)\)}. \quad \blacksquare \\ \end{align*} \]